Synthesis and characterization of Zn-doped LiCoO2 material prepared via glycine-nitrate combustion method for proton conducting solid oxide fuel cell application - Wan Nor Anasuhah Wan Yusof,; Abdullah Abdul Samat,; Nur Wardah Norman,; Mahendra Rao Somalu,; Andanastuti Muchtar,; Nurul Akidah Baharuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
LiCo2 -based materials are well-known, widely used as cathode materials in lithium ion batteries and currently are also used in low temperature proton conducting solid oxide fuel cells (H+-SOFCs) application. Dopants such as Zn are introduced in LiCo2 -based materials to improve the properties and performance of the materials for H+-SOF Capplication. In this study, Zn-doped LiCo2 , LiCo0.6 Zn0.4O2 (LCZO) powder was synthesized via glycine-nitrate combustion method followed by various characterizations. The precursor LCZO powder dried at 100°C was subjected to thermogravimetric analysis (TGA). The phase formation and morphology of the calcined LCZO powder at 600°C were examined by an X-ray diffractometer (XRD) and a tabletop scanning electron microscope (SEM), respectively. The TGA result revealed that the thermal decomposition of the intermediate compounds in the precursor LCZO powder was completed at 800°C through three main phases of weight losses. A pure phase of LCZO was not completely produced after the calcination at 600°C due to the presence of secondary phases as confirmed from the XRD analysis. The identified secondary phases that present are confirmed as ZnCo2 O4 and ZnO as documented in JCPDS file no. 00-001-1149 and JCPDS file no. 01-079-0205 consecutively. The SEM images showed that the impure calcined LCZO powder possessed homogeneous and fine particles.